Guillain-Barre Syndrome Following Ad26.Cov2.S Covid-19 Vaccine: A Case Report - Khanal, Sushmita; Khanal, Sunil Babu (Journal of Nobel Medical College, 2021)
Guillain-Barre Syndrome has been reported as a rare side effect in the recipients of Johnson & Johnson®’s Janssen Ad26.COV2.S COVID-19 vaccine. We report a case of Guillain-Barre Syndrome in a 50 years old female following the administration of the aforementioned vaccine.